Pengaruh Kompensasi Finansial dan Kompensasi Non Finansial Terhadap Kinerja Karyawan PG Djombang Baru - Ahmad Muizzuddin; Mahfudiyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to determine the effect of financial or financial compensation and non-financial compensation on employee performance at PG. New Djombang. The method applied in this study is a number-based research method and uses a causal approach or cause and effect relationship. The number of samples taken was 60 employees using a comprehensive sampling technique. The data collection technique used was a questionnaire. Hypothesis testing is carried out using the t test, F test, and test R. The findings of this research show (1)that Financial Compensation has a positive influence on Employee Performance at PG Djombang Baru (2)Non-Financial Compensation has a positive effect on employee performance at PG Djombang Baru (3) Financial Compensation and non-Financial compensation have a simultaneous effect on Employee Performance at PG Djombang Baru